Shear stress at a compliant model of the human carotid bifurcation - Jones, Steve A.; Giddens, Don P.; Anayiotos, Andreas (My University, 1994)
To investigate the role of a compliant wall to the near wall hemodynamic flowfield, two models of the carotid bifurcation were constructed. Both were of identical internal geometries, however, one was made of compliant material which produced approximately the same degree of wall motion as that occurring in vivo while the other one was rigid. The inner geometries were formed from the same mold so that the configurations are directly comparable. Each model was placed in a pulsatile flow system that produced a physiologic flow waveform. Velocity was measured with a single component Laser system and wall shear rate was estimated from near wall data. Wall motion in the compliant model was measured by a wall motion transducer and the maximum diameter change varied between 4-7 percent in the model with the greatest change at the axis intersection. The mean shear stress in the compliant model was observed to be smaller by about 30 percent at most locations. The variation in peak shear stress was greater and occasionally reached as much as 100 percent with the compliant model consistently having smaller positive and negative peaks. The separation point was seen to move further upstream in the compliant cast. The modified flowfield in the presence of a compliant wall can then be important in the hemodynamic theory of atherogenesis. To investigate the role of a compliant wall to the near wall hemodynamic flowfield, two models of the carotid bifurcation were constructed. Both were of identical internal geometries, however, one was made of compliant materials which produced approximately the same degree of wall motion as that occurring in vivo while the other one was rigid. The inner geometries were formed from the same mold so that the configurations are directly comparable. Each model was placed in a pulsatile flow system that produced a physiologic flow waveform. Velocity was measured with a single component Laser system and wall shear rate was estimated from near wall data. Wall motion in the compliant model was measured by a wall motion transducer and the maximum diameter change varied between 4-7 percent in the model with the greatest change at the axis intersection. The mean shear stress in the compliant model was observed to be smaller by about 30 percent at most locations. The variation in peak shear stress was greater and occasionally reached as much as 100 percent with the compliant model consistently having smaller positive and negative peaks. The separation point was seen to move further upstream in the compliant cast. The modified flow field in the presence of a compliant wall can the be important in the hemodynamic theory of atherogenesis.
Keywords: Cardiovascular system; Transducers; Hemodynamics; Blood